Divinization and Technology
1 online resource (212 pages)
Keywords: This book offers a political anthropological discussion of subversion, exploring its imbrication with technological and divinization practices, and uncovering some of its particular effects on human existence, from prehistory until the contemporary age. Subversion is often romanticized as a means of opposing or undermining power in the name of supposedly universal values, yet techniques of subversion are actually deployed by people of all modern political and philosophical persuasions. With subversion having become a tool of mainstream ‘power’ that threatens to dominate social and political reality and so render the populace servile and subject to a generalized culture industry, Divinization and Technology examines the ways in which technology and divinization, withtheir efforts to unite with divine powers, can be brought together as modalities of subversion.